The EC internal market, Lomé IV and the ACP countries - Stefan Brüne (Intereconomics, 1990)
The implications that the internal market could hold for the EC's foreign trade relations are a cause of considerable worry to countries in the Third World. Particularly the ACP countries, for many of whom the EC is their foremost product and import market, fear the possible strengthening of protectionist barriers and a Europe increasingly preoccupied with itself. This article examines the perspectives of EC-ACP trade relations in the light of the Lomé IV agreement.
Keywords: 330; North-South Relations